Ã˜ÂªÃ˜Â·Ã™Ë†Ã™Å Ã˜Â± Ã˜Â§Ã™â€žÃ˜Â´Ã˜Â®Ã˜ÂµÃ™Å Ã˜Â© Ã˜Â¨Ã˜Â§Ã™â€žÃ˜Â£Ã™Ë†Ã˜ÂµÃ˜Â§Ã™Â Ã˜Â§Ã™â€žÃ™Ë†Ã˜Â§Ã˜Â±Ã˜Â¯Ã˜Â© Ã˜Â§Ã™â€žÃ™â€¦Ã™â€¡Ã™â€¦Ã˜Â© Ã™ÂÃ™Å Ã˜Â§Ã™â€žÃ˜Â£Ã˜ÂÃ˜Â§Ã˜Â¯Ã™Å Ã˜Â« Ã˜Â§Ã™â€žÃ™â€ Ã˜Â¨Ã™Ë†Ã™Å Ã˜Â© - Mamun, Abdullah Al (Ar Raniry : International Journal of Islamic Studies, 2018)
Ã™Æ’Ã™â€žÃ™â€ Ã˜Â§ Ã™Å Ã˜Â¹Ã™â€žÃ™â€¦ Ã˜Â£Ã™â€ Ã™â€˜ Ã˜Â§Ã™â€žÃ™â€žÃ™â€¡ Ã˜Â¨Ã˜Â¹Ã˜Â« Ã™â€¦Ã˜ÂÃ™â€¦Ã˜Â¯Ã˜Â§ Ã˜ÂµÃ™â€žÃ™â€° Ã˜Â§Ã™â€žÃ™â€žÃ™â€¡ Ã˜Â¹Ã™â€žÃ™Å Ã™â€¡ Ã™Ë†Ã˜Â³Ã™â€žÃ™â€¦ Ã˜Â¥Ã™â€žÃ™Å Ã™â€ Ã˜Â§ Ã™â€žÃ™â€¡Ã˜Â¯Ã˜Â§Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ™â€ Ã˜Â§Ã˜Â³ Ã˜Â¥Ã™â€žÃ™â€° Ã™â€¦Ã˜Â§ Ã™â€¡Ã™Ë† Ã˜Â®Ã™Å Ã˜Â± Ã™ÂÃ™Å  Ã˜Â§Ã™â€žÃ˜Â¯Ã™â€ Ã™Å Ã˜Â§ Ã™Ë†Ã˜Â§Ã™â€žÃ˜Â¢Ã˜Â®Ã˜Â±Ã˜Â©, Ã™â€¦Ã˜Â¹ Ã˜Â£Ã™â€ Ã™â€¡ Ã™Æ’Ã˜Â§Ã™â€  Ã˜Â®Ã™Å Ã˜Â± Ã˜Â§Ã™â€žÃ™â€ Ã˜Â§Ã˜Â³ Ã™ÂÃ™Å  Ã˜Â¸Ã˜Â±Ã™Ë†Ã™Â Ã˜Â§Ã™â€žÃ˜ÂÃ™Å Ã˜Â§Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â¨Ã˜Â´Ã˜Â±Ã™Å Ã˜Â© Ã™Æ’Ã™â€žÃ™â€¡Ã˜Â§ Ã™Ë†Ã™ÂÃ™Å  Ã˜ÂÃ™Å Ã˜Â§Ã˜ÂªÃ™â€¡ Ã˜Â£Ã˜Â³Ã™Ë†Ã˜Â© Ã˜ÂÃ˜Â³Ã™â€ Ã˜Â© Ã™Ë†Ã™â€šÃ˜Â¯Ã™Ë†Ã˜Â© Ã™Æ’Ã˜Â§Ã™â€¦Ã™â€žÃ˜Â©, Ã™Ë†Ã™â€žÃ™Å Ã˜Â³ Ã™â€¡Ã™â€ Ã˜Â§Ã™Æ’ Ã˜Â´Ã™Å Ã˜Â¦ Ã™â€¦Ã˜Â§ Ã™â€žÃ˜Â§ Ã™ÂÃ™Å Ã™â€¡ Ã™â€¡Ã˜Â¯Ã™Å Ã™â€¡ Ã™Ë†Ã˜Â³Ã™â€ Ã˜ÂªÃ™â€¡ Ã™â€¦Ã™â€  Ã˜Â§Ã™â€žÃ˜Â£Ã™â€šÃ™Ë†Ã˜Â§Ã™â€ž Ã™Ë†Ã˜Â§Ã™â€žÃ˜Â£Ã™ÂÃ˜Â¹Ã˜Â§Ã™â€ž Ã™Ë†Ã˜Â§Ã™â€žÃ˜ÂªÃ™â€šÃ˜Â§Ã˜Â±Ã™Å Ã˜Â± Ã™Ë†Ã˜Â§Ã™â€žÃ˜ÂµÃ™ÂÃ˜Â§Ã˜Âª Ã˜Â®Ã™â€žÃ™â€šÃ™Å Ã˜Â© Ã™Æ’Ã˜Â§Ã™â€ Ã˜Âª Ã˜Â£Ã™Ë† Ã˜Â®Ã™â€žÃ™â€šÃ™Å Ã˜Â©, Ã™ÂÃ™Æ’Ã˜Â°Ã™â€žÃ™Æ’ Ã™ÂÃ™Å  Ã˜ÂªÃ˜Â·Ã™Ë†Ã™Å Ã˜Â± Ã˜Â§Ã™â€žÃ˜Â´Ã˜Â®Ã˜ÂµÃ™Å Ã˜Â© Ã˜Â£Ã™Å Ã˜Â¶Ã˜Â§, Ã™ÂÃ™ÂÃ™Å  Ã˜ÂÃ™Å Ã˜Â§Ã˜ÂªÃ™â€¡ Ã™â€ Ã˜Â¬Ã˜Â¯ Ã™Æ’Ã™â€¦Ã˜Â§Ã™â€žÃ˜Â© Ã˜Â§Ã™â€žÃ˜Â´Ã˜Â®Ã˜ÂµÃ™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂªÃ™Å  Ã™Å Ã˜Â¯Ã™â€¡Ã˜Â´ Ã˜Â§Ã™â€žÃ™â€ Ã˜Â§Ã˜Â³ Ã˜Â¨Ã™â€¡Ã˜Â§ Ã˜Â¹Ã˜Â¨Ã˜Â± Ã˜Â§Ã™â€žÃ™â€šÃ˜Â±Ã™Ë†Ã™â€  Ã™Æ’Ã™â€žÃ™â€¡Ã˜Â§, Ã™ÂÃ˜Â¥Ã˜Â°Ã˜Â§ Ã˜ÂªÃ˜Â£Ã™â€¦Ã™â€žÃ™â€ Ã˜Â§ Ã™ÂÃ™Å  Ã˜Â£Ã™â€šÃ™Ë†Ã˜Â§Ã™â€žÃ™â€¡ Ã™Ë†Ã˜Â£Ã™ÂÃ˜Â¹Ã˜Â§Ã™â€žÃ™â€¡ Ã™Ë†Ã˜ÂªÃ™â€šÃ˜Â±Ã™Å Ã˜Â±Ã˜Â§Ã˜ÂªÃ™â€¡ Ã™Ë†Ã˜ÂµÃ™ÂÃ˜Â§Ã˜ÂªÃ™â€¡ Ã˜Â¹Ã˜Â«Ã˜Â±Ã™â€ Ã˜Â§ Ã˜Â¹Ã™â€žÃ™â€° Ã˜Â¨Ã˜Â¹Ã˜Â¶ Ã˜Â§Ã™â€žÃ˜Â£Ã™Ë†Ã˜ÂµÃ˜Â§Ã™Â Ã˜Â§Ã™â€žÃ™â€¦Ã™â€¡Ã™â€¦Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â£Ã˜Â³Ã˜Â§Ã˜Â³Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂªÃ™Å  Ã˜ÂªÃ˜Â³Ã˜Â§Ã˜Â¹Ã˜Â¯ Ã˜Â§Ã™â€žÃ™â€ Ã˜Â§Ã˜Â³ Ã˜Â¹Ã™â€žÃ™â€° Ã˜ÂªÃ™Æ’Ã™Ë†Ã™Å Ã™â€  Ã˜Â§Ã™â€žÃ˜Â´Ã˜Â®Ã˜ÂµÃ™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â±Ã˜Â§Ã˜Â¦Ã˜Â¹Ã˜Â© Ã˜Â§Ã™â€žÃ™â€šÃ™Ë†Ã™Å Ã˜Â© Ã™Ë†Ã˜ÂªÃ˜Â·Ã™Ë†Ã™Å Ã˜Â±Ã™â€¡ Ã™â€¦Ã˜Â§ Ã™â€žÃ™â€¦ Ã™Å Ã˜Â¬Ã˜Â¯ Ã˜Â§Ã™â€žÃ™â€ Ã˜Â§Ã˜Â³ Ã˜Â¥Ã™â€žÃ˜Â§ Ã˜Â¨Ã˜Â¹Ã˜Â¯ Ã˜Â·Ã™â€žÃ™Ë†Ã˜Â¹ Ã˜Â´Ã™â€¦Ã˜Â³ Ã˜Â§Ã™â€žÃ™â€¡Ã˜Â¯Ã˜Â§Ã™Å Ã˜Â© Ã™ÂÃ™Å  Ã™â€¦Ã™Æ’Ã˜Â© Ã˜Â§Ã™â€žÃ™â€¦Ã™Æ’Ã˜Â±Ã™â€¦Ã˜Â©, Ã™ÂÃ™ÂÃ™Å  Ã™â€¡Ã˜Â°Ã˜Â§ Ã˜Â§Ã™â€žÃ˜Â¨Ã˜ÂÃ˜Â« Ã™â€ Ã™â€žÃ˜Â§Ã˜ÂÃ˜Â¸ Ã˜ÂªÃ™â€žÃ™Æ’ Ã˜Â§Ã™â€žÃ˜Â£Ã™Ë†Ã˜ÂµÃ˜Â§Ã™Â Ã˜Â§Ã™â€žÃ™â€¦Ã™â€¡Ã™â€¦Ã˜Â© Ã˜Â§Ã™â€žÃ™Ë†Ã˜Â§Ã˜Â±Ã˜Â¯Ã˜Â© Ã™ÂÃ™Å  Ã˜Â§Ã™â€žÃ˜Â£Ã˜ÂÃ˜Â§Ã˜Â¯Ã™Å Ã˜Â« Ã˜Â§Ã™â€žÃ˜Â´Ã˜Â±Ã™Å Ã™ÂÃ˜Â© Ã™Ë†Ã™â€ Ã™â€šÃ˜Â³Ã™â€¦Ã™â€¡Ã˜Â§ Ã˜Â¹Ã™â€žÃ™â€° Ã˜Â§Ã™â€žÃ˜Â£Ã˜Â±Ã˜Â¨Ã˜Â¹Ã˜Â© Ã™Ë†Ã™â€¡Ã™Å  Ã˜Â§Ã™â€žÃ˜Â£Ã™Ë†Ã˜ÂµÃ˜Â§Ã™Â Ã˜Â§Ã™â€žÃ˜Â¹Ã™â€šÃ™â€žÃ™Å Ã˜Â© Ã™Ë†Ã˜Â§Ã™â€žÃ˜Â£Ã™Ë†Ã˜ÂµÃ˜Â§Ã™Â Ã˜Â§Ã™â€žÃ˜Â¨Ã˜Â¯Ã™â€ Ã™Å Ã˜Â© Ã™Ë†Ã˜Â§Ã™â€žÃ˜Â£Ã˜Â®Ã™â€žÃ˜Â§Ã™â€š Ã˜Â§Ã™â€žÃ˜ÂÃ˜Â³Ã™â€ Ã˜Â© Ã™Ë†Ã˜Â§Ã™â€žÃ˜Â£Ã™Ë†Ã˜ÂµÃ˜Â§Ã™Â Ã˜Â§Ã™â€žÃ˜Â§Ã˜Â¬Ã˜ÂªÃ™â€¦Ã˜Â§Ã˜Â¹Ã™Å Ã˜Â© Ã˜Â«Ã™â€¦ Ã™â€ Ã™ÂÃ˜ÂµÃ™â€žÃ™â€¡Ã˜Â§ Ã™â€¦Ã˜Â¹ Ã˜Â§Ã™â€žÃ™â€ Ã˜ÂµÃ™Ë†Ã˜Âµ Ã˜Â§Ã™â€žÃ™â€¦Ã˜ÂªÃ˜Â¹Ã™â€žÃ™â€šÃ˜Â© Ã˜Â¨Ã™â€¡Ã˜Â§ Ã™â€žÃ™Å Ã˜ÂªÃ˜Â¶Ã˜Â Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â±Ã˜Â§Ã™â€¦ Ã™â‚¬